ELT materials transformed: Exploring outcome-based education elements in high school EFLtextbooks - Pulungan, Anni Holila; Jasni Kharisma, Adib; Kusmanto, Joko; Ginting, Pirman (Universitas Ahmad Dahlan, 2024)
Infusing outcome-based components such as advanced communication, productivity and accountability, critical thinking, creativity, collaboration, and flexibility and adaptability are deemed critical in a textbook. Conversely, the evidence revealed shortcomings in certain aspects of textbooks, as exemplified by the